Pembelajaran Bahasa Indonesia dengan Metode Struktural Analitik Sintetik (Sas) Siswa Kelas I di SDIT Brilliant Kecamatan Mojoagung - Alifah, Faridahtul; Supratno, Haris; Dwi Rochmania, Desty (IJPSE : Indonesian Journal of Primary Science Education, 2021)
The focus in this research is learning Indonesian with Synthetic Analytical Structural (SAS) method. The main purpose of this research was to improve participant’s knowledge about Indonesian with SAS method. It used pretest and posttest to know the effect of SAS method in learning Indonesian and use the result as the main indicator. It used quantitative and qualitative research design. The subject of this research is the first grade students and teachers of SDIT Brilliant, Mojoagung, Jombang joining. There were two meetings conducted. The instruments used in each meetings was consisted of observation sheet of participants activity, study record, interview, and documentation. The researh showed that there was a significant effect of using SAS method to learn Indonesian on Tematic 5, subtheme 1, at the second meeting. It is shown from the pretest which get 70,2%, categorized as enough and the posttest get 85,8%, categorized as excellent. Based on the data, it can be concluded that learning Indonesian with SAS method have a good impact on students performance and it is proven with the good score as the outcomes. Keywords : Indonesian subjects, Synthetic Analytical Structural (SAS) method.